The Effect of Tibial Rotation on the Contribution of Medial and Lateral Hamstrings During Isometric Knee Flexion - Jónasson, Gunnlaugur (Sports Health, 2015)
BACKGROUND: Selective atrophy of hamstring components may result from muscle strain or graft harvesting for anterior cruciate ligament reconstruction. Assessment and rehabilitation that specifically targets medial (MH) or lateral (LH) hamstring components may improve patient outcomes. The purpose of this study was to evaluate effects of volitional tibial rotation medially (MR) versus laterally (LR) on activation levels of MH versus LH and strength measures during isometric testing of knee flexors. HYPOTHESIS: Muscle activation of MH and LH during knee flexor strength testing will be augmented when coupled with MR and LR of the tibia, respectively, without affecting knee flexor strength measures. STUDY DESIGN: Cross-sectional laboratory study. LEVEL OF EVIDENCE: Level 3. METHODS: Surface electrodes were used to record neuromuscular activity from MH and LH of the right lower limb in 40 healthy young men and women during isometric knee flexor strength testing at 40° of knee flexion, where participants maintained concurrent volitional MR or LR of the tibia. Statistical analyses of variance included general linear models for repeated measures. RESULTS: A significant interaction was found for tibial rotation and hamstring component variables (P < 0.01). When isometric knee flexion was coupled with LR, normalized activation levels were similar for MH and LH. When performed with MR, a significant drop in LH activation led to dissimilar activation levels of the 2 components. Significantly greater strength measures were found when isometric knee flexion was performed with concurrent LR of the tibia (P < 0.01). Both sexes demonstrated the same rotation-dependent differences. CONCLUSION: Coupling tibial rotation with knee flexor activities primarily affects the LH component. CLINICAL RELEVANCE: Strategies involving volitional tibial rotation may be considered for specific assessment/rehabilitation of the MH or LH component.